2018
DOI: 10.1109/tdei.2018.006938
|View full text |Cite
|
Sign up to set email alerts
|

Streamer characteristic and breakdown in a mineral oil and a synthetic ester liquid under DC voltage

Abstract: This paper presents experimental studies of streamer propagation and breakdown in a mineral oil and a synthetic ester liquid under both positive and negative DC voltages. A point-plane electrode configuration with a tip radius of 10 µm was used. Characteristics of streamer length, propagation velocity and shape were analysed based on shadowgraph images obtained at a gap distance of 10 mm using a multi-channel ultra-high speed camera. Under positive polarity, the streamers in both liquids propagate in the 2 nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…With an increase in propagation velocity, streamers' shape and light also change. The spatial shapes and oscillography of streamers have been investigated and analyzed in accordance with propagation velocities, electrode gaps, and acceleration voltages in mineral oil and synthetic esters [73], [74]. Synthetic esters were found to be inferior to mineral oils in resisting the growth of a streamer.…”
Section: Pre-breakdown Phenomenamentioning
confidence: 99%
“…With an increase in propagation velocity, streamers' shape and light also change. The spatial shapes and oscillography of streamers have been investigated and analyzed in accordance with propagation velocities, electrode gaps, and acceleration voltages in mineral oil and synthetic esters [73], [74]. Synthetic esters were found to be inferior to mineral oils in resisting the growth of a streamer.…”
Section: Pre-breakdown Phenomenamentioning
confidence: 99%
“…However, a synthetic ester is comparable quantitively with mineral oil. Xiang et al [76] reported totally different conclusions concerning the DC-BDV. These conclusions were based on measurements in a point-to-sphere electrode arrangement representing non-uniform electrical field distributions.…”
Section: Ac and DC Breakdown Voltagementioning
confidence: 99%
“…However, the obtained results in each case exceed 60 kV, which is enough of a value for the dielectric liquids to be applied in devices of nominal voltages equal to 69 kV or higher. The available data are limited in the case of DC stress-based tests of synthetic esters [75][76][77]. In [75,77] the authors compared simply the DC-BDV between selected types of dielectric liquids and their mixtures in a quasi-uniform electric field created by a sphere-to-sphere electrode system.…”
Section: Ac and DC Breakdown Voltagementioning
confidence: 99%
“…Most previous investigations focused on conductivity caused by oil contamination. Other researchers investigated the influence of LI on streamer characteristics (with and without pressboard interface) or the breakdown and withstand voltage of various insulating oils in a field [23]. One study examined the effects of electrodes, impulse shape, nature of dielectric liquid and cellulose particles [24].…”
Section: Introductionmentioning
confidence: 99%